Індекс демократичних виборів в Україні - Бучин, Микола (Видавництво Львівської політехніки, 2014)
На основі розробленої комплексної моделі демократичних виборів досліджено її особливості в Україні. Використовуючи власну методику, автор обчислює Індекс демократичних виборів під час виборчих кампаній в Україні. Індекс є відносною величиною, що показує відповідність реального стану конкретних українських виборчих перегонів ідеальній моделі демократичних виборів. In the article the author on the basis of the designed comprehensive model of democratic elections researches its peculiarities in Ukraine. The model is based on democratic principles of elections. On the basis of their analysis the author distinguishes the indicators of democratic elections, in other words, the conditions of realization of elections, observance or nonobservance of which will testify to the level of democratic character of electoral process. Each indicator is divided into constituents. They can be considered in two planes: in the sphere of legislation (de jure constituents) and in the sphere of electoral practice (de facto constituents). It gives an opportunity to fully describe the institute of democratic elections and define its Index. Each of democratic principles of elections, indicators, and their constituents has its appropriated amount of points according to their «weight», importance in providing the democratic character of elections. The author introduces into a scientific circulation such category as Index of democratic elections. It is a relative value that shows accordance of the real state of particular electoral races to the ideal model of democratic elections. The Index of democratic elections can acquire a numerical value from 0 (elections are fully undemocratic) to 1 (elections are fully democratic). Using own methodology, the author examines the peculiarities of electoral campaigns in Ukraine from 1990 to present time, calculates Index of democratic elections in our state. It is found out, that until 2004 the Index of democratic elections had been declining. After «orange revolution» the level of democratic character of elections grew substantially, however, since 2007 it has been gradually declining again.
An index of democratic elections in Ukraine
Keywords: демократія; вибори; виборче законодавство; виборча практика; демократичні принципи виборів; демократичні принципи виборів; індикатори демократичних виборів; Індекс демократичних виборів; democracy; elections; electoral legislation; electoral practice; democratic principles of elections; indicators of democratic elections; Index of democratic elections